The origins and evolution of Islamic law - Hallaq, Wael B (Cambridge University, 2013)
Covering more than three centuries of legal history, this study presents an important account of how Islam developed its own law from ancient Near Eastern legal cultures, Arabian customary law and Quranic reform. The book explores the interplay between law and politics, demonstrating how the jurists and ruling elite led a symbiotic existence that paradoxically allowed Islamic law to become uniquely independent of the "state."